Optimalisasi Perencanaan Persediaan Obat Esensial Menggunakan Analisis ABC (Always Better Control) dan Metode Peramalan untuk Mengurangi Kekosongan Stok di Rumah Sakit XYZ - Ika Bana Purba; Anjel Agita Br Ginting; Anita Christine Sembiring (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2026)
Essential medicines are an integral component of the healthcare system, as their consistent availability is crucial for successful therapy and patient safety. Observations at the Royal Prima Medan Hospital Pharmacy Warehouse identified stockouts, emergency drug purchases (cito), and drug borrowing from other hospitals. This study employed a quantitative descriptive approach to classify essential medicines into Classes A, B, and C using ABC analysis and to forecast demand for Class A medicines over the next six months. Class A, comprising the first three items, accounted for approximately 80% of the total budget and required intensive monitoring. Class B, comprising the next seven items, accounted for approximately 15% of the budget and required periodic monitoring, while Class C, comprising the last ten items, accounted for approximately 5% and required less intensive supervision. The six-month demand forecast for Class A medicines yielded average monthly demands of 6,875.59 units for Ceftriaxone 1 g, 15,789.35 units for Cefixime 200 mg, and 16,971.30 units for Ondansetron 4 mg. These findings provide a basis for improving inventory planning and reducing stockout occurrences.